Asuhan Kebidanan Komunitas Pada Keluarga Tn “A” Dengan Anemia Pada Ibu Hamil Di Desa Pemepek Kecamatan Priggarata - Baiq Putri Istiazah; Gladeva Yugi Antari (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Anemia is a serious complication that can increase the risk of material and child mortality. The main causes of anemia are iron deficiency and increased blood plasma volume. This research was conducted through community service by providing education on the prevention of anemia in pregnant women using poster media. The result showed that health education can improve mothers’ knowledge about anemia prevention, pregnant women who attended health education promised to maintain a healthy lifestyle, take blood supplement tablets and get enough rest. Health education and effective communication can improve the awareness and health of pregnant women in preventing anemia. Compliance in consuming nutritious food and blood supplement tablets is very important in preventing anemia in pregnant women.